-10k-16k-16k-2k=12

Simple and best practice solution for -10k-16k-16k-2k=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10k-16k-16k-2k=12 equation:



-10k-16k-16k-2k=12
We move all terms to the left:
-10k-16k-16k-2k-(12)=0
We add all the numbers together, and all the variables
-44k-12=0
We move all terms containing k to the left, all other terms to the right
-44k=12
k=12/-44
k=-3/11

See similar equations:

| x*4.4=9000 | | x2+2=35 | | 10^x+6=55 | | 3+1/3=8+2/3x | | -6x+(-30)=18 | | 2/3n-156=313/24 | | -5k-11=-86 | | 9+5-8r=-2-6r | | 17u=40+9u | | (v)-1=4/3 | | 18t-15t=9 | | 150*x=6 | | 5x2+X=35 | | 5x2+2X=35 | | -7v=-9v+8 | | B=(6/13)y | | 6n-(5n-1)=4 | | 11-3b/5=1/3b | | 2x+2x=2=4x=2 | | (x-4/10)=(3/5)(-x-5/15) | | (13x+3)=(3x+21) | | B=(6÷13)y | | -7+7j=6j | | x2+1X=35 | | 4(2r-1)=–2(3r+16) | | ​x​–1.4=-6.3 | | -10-4s=-6s+10 | | (42-6)*10=x | | 120+0.30x=60+0.60x | | 42-6=10+10x | | 8=(3/4a+12-a+4 | | x2-1X=35 |

Equations solver categories